Evaluation of Cardiac Circadian Rhythm Deconditioning Induced by 5-to-60 Days of Head-Down Bed Rest - Solbiati, Sarah; Martin-Yebra, Alba; Vaïda, Pierre; Caiani, Enrico G. (Frontiers in Physiology, 2021)
Head-down tilt (HDT) bed rest elicits changes in cardiac circadian rhythms, generating possible adverse health outcomes such as increased arrhythmic risk. Our aim was to study the impact of HDT duration on the circadian rhythms of RR and QT intervals from 24-hour Holter ECG recordings acquired in 63 subjects during six different HDT bed rest campaigns of SHORT (5-day), MID (21-day) and LONG (60-day) duration. Circadian rhythms of RR and QTend series were evaluated by Cosinor analysis, resulting in a value of midline (MESOR), oscillation amplitude (OA) and acrophase (𝜑). In addition, the QTc (Bazett) was computed, and day-time, night-time, maximum and minimum RR, QTend and QTc were calculated. Several analyses were conducted, comparing: (1) the effects of HDT5, HDT21 and HDT58 with baseline (PRE); (2) trends in recovery period at post-HDT epochs (R) in SHORT, MID and LONG separately vs PRE; (3) differences at R+0 due to bed rest duration; (4) abrupt changes between the last HDT acquisition and the respective R+0 in SHORT, MID and LONG. During HDT, major changes were observed at HDT5, with increased RR and QTend MESOR, mostly related to a diurnal lengthening and increased minima, while the QTc shortened. Afterwards, a progressive adjustment was observed with HDT progression. Additionally, the 𝜑 anticipated, and the OA was reduced during the entire HDT, decreasing system’s ability to react to incoming stimuli. The restoration of the orthostatic position elicited the shortening of RR and QTend together with QTc prolongation, notwithstanding the period spent in HDT. However, the magnitude of post-HDT changes, as well as the difference between the last HDT day and R+0, showed a trend to increase with increasing HDT duration, and 5/7 days were not sufficient for recovering after LONG. Additionally, the 𝜑 postponed, and the OA significantly increased at R+0 after SHORT and LONG, possibly increasing the arrhythmic risk. These results provide evidence that continuous monitoring of astronauts’ circadian rhythms, and further investigations on possible measures for counteracting the observed modifications, will be key for future missions including long periods of weightlessness and gravity transitions, for preserving astronauts’ health and mission success.